PARTICIPATORY DISASTER RISK MAPPING OF THE LEMBANG FAULT AREA - Satya Raharjo, Anggito
Disaster risk mapping is a key step in disaster mitigation and impact reduction efforts, especially for disaster-prone areas like the Lembang Fault Zone. The capstone project aims to participatively mapping of disaster risks in the Lembang Fault Zone, involving local communities in data collection and analysis processes. The study area for this disaster risk mapping includes 19 neighborhoods in 4 villages: Gudangkahuripan, Lembang, Pagerwangi, and Langensari. The resulting disaster risk map will be presented on a large scale, as there is currently no large-scale disaster risk map available for this region. The methods used in this project include field surveys, direct interviews, and processing secondary data. All this data will be used to calculate the various indicators that contribute to disaster risk factors, such as hazards, vulnerability, and capacity. The data will be processed and analysed using Geographic Information Systems to produce a well-constructed disaster risk map. The results indicate that 19 neighborhoods in the Lembang Fault Zone have a high average risk index for earthquakes and a moderate risk level for landslides. The generated disaster risk map is expected to serve as a foundation for disaster mitigation planning and decision-making in the Lembang Fault Zone, as well as raise public awareness of potential disasters in the area.